Regenerative periodontics in restoring oral functions: A power to regenerate what's lost - Hunny Sharma; Swati Verma (Wolters Kluwer Medknow Publications, 2018)
Although human oral cavity benefits from remarkable mechanical and functional properties, still it faces continuous insult and damage resulting from exposure to microbial attacks. In the past where conventional dentistry was only focused on evaluating, restoration, and replacement of the diseased oral structures. The recent era of advancement in the field of materials science, molecular biology, tissue engineering, and stem cell research's had let to the path of development of new era of periodontal engineering known as regenerative periodontics. The ultimate goal of regenerative periodontics is the regeneration of the lost periodontium due to advanced periodontal disease. Currently, scientists are working on a wide range of biomaterials and scaffolds, genes, stem cells, and growth factors in the hope of achieving more predictable outcomes in regenerative periodontics. Future research areas in regenerative periodontics include three-dimensional printing, tissue engineering, and gene therapy strategies which give more positive and predictable outcomes of regenerative periodontics. This review provides an overview of current on-going technique and researches in the field of regenerative periodontics and also will show a glimpse of what the future holds.